The Composition, Diversity and Predictive Metabolic Profiles of Bacteria Associated With the Gut Digesta of Five Sea Urchins in Luhuitou Fringing Reef (Northern South China Sea) - Yao, Qiucui; Yu, Kefu; Liang, Jiayuan; Wang, Yinghui; Hu, Baoqing; Huang, Xueyong; Chen, Biao; Qin, Zhenjun (Frontiers in Microbiology, 2019)
Sea urchins strongly affect reef ecology, and the bacteria associated with their gut digesta have not been well studied in coral reefs. In the current study, we analyze the bacterial composition of five sea urchin species collected from Luhuitou fringing reef, namely Stomopneustes variolaris, Diadema setosum, Echinothrix calamaris, Diadema savignyi, and Tripneustes gratilla, using high-throughput 16S rRNA gene-based pyrosequencing. Propionigenium, Prolixibacter, and Photobacterium were found to be the dominant bacterial genera in all five species. Interestingly, four sea urchin species, including S. variolaris, D. setosum, E. calamaris and D. savignyi, displayed a higher mean total abundance of the three bacterial genera (69.72 ± 6.49%) than T. gratilla (43.37 ± 13.47%). Diversity analysis indicated that the gut digesta of sea urchin T. gratilla displayed a higher bacterial α-diversity compared with the other four species. PCoA showed that the four groups representing D. setosum, D. savignyi, E. calamaris, and S. variolaris were overlapping, but distant from the group representing T. gratilla. Predictive metagenomics performed by PICRUSt revealed that the abundances of genes involved in amino acid metabolism and metabolism of terpenoid and polyketide were higher in T. gratilla, while those involved in carbohydrate metabolism were higher in the other four sea urchin species. Therefore, our results indicated that the composition, diversity and predictive metabolic profiles of bacteria associated with the gut digesta of T. gratilla were significantly different from those of the other four sea urchin species in Luhuitou fringing reef.